PENGARUH CELEBRITY ENDORSEMENT PADA MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN MENGINAP TAMU DI HOTEL THE WESTIN RESORT NUSA DUA, BALI (Jurnal Destinasi Pariwisata, 2026)
This study investigates the influence of celebrity endorsement on Instagram on guests' decision to stay at a five-star premium brand hotel, The Westin Resort Nusa Dua, Bali. A premium five-star hotel is defined as a luxury establishment with international standards, exclusive services, and comprehensive facilities, professionally managed to provide accommodation and various amenities for guests.The population for this study comprised all guests who stayed at The Westin Resort Nusa Dua, Bali, in 2024, totaling 176,488 individuals. A sample of 100 participants was determined using the Slovin formula and selected through purposive sampling. The key criterion for participant selection was that they must have previously stayed at The Westin Resort Nusa Dua, Bali. Data were collected via questionnaires and analyzed using simple linear regression.The findings indicate that celebrity endorsement has a significant positive influence on guests' decision to stay at The Westin Resort Nusa Dua. This suggests that the more effective the celebrity endorsement is, the more likely it is to increase guests' decisions to book a stay at the hotel.
Keywords: Celebrity Endorsement; Keputusan Menginap; Hotel